A substituição da contribuição sindical obrigatória pela contribuição negocial aprovada em assembleia, por decisão judicial : um caminho para a plena eficácia da liberdade sindical no Brasil - Meneses, Luiz Manoel Andrade (2017)
The work pursues a way to the concretization of the fundamental right to labor union liberty in Brazil. The Convention 87 of International Labor Organization - ILO, which treats of Union Liberty, was not ratified by Brazil, which maintains the system of union unicity to the labor unions, vinculated to the obligatory union contribution. The referred convention is inserted in 1998 ILO Declaration on Fundamental Principles an Rights, which integrates ILO’s Constitution. Therefore, this non-ratification affronts the fundamental right of employee and contradicts Brazil’s participation as a Member State of International Labor Organization. However, national courts must pay attention to the International Labor Law to solve litigations. In this matter, the vision of International Labor Organization is presented, found in decisions of national courts, with diverse possibilities of International Labor Law application. Under the optic of internal law, the Theory of Material Opening of Fundamental Rights Catalogues on Brazilian Constitution is studied as an instrument to the efficacy of union liberty in Brazil. In this context, even with other fundaments, recent jurisprudence of the Superior Labor Court - SLC applied the decisions of International Labor Organization’s Committee on Freedom of Association and admitted the substitution of the obligatory union contribution by the union contribution approved in Assembly, indicating a way to concretize union liberty. The relevance and the potential of this way is demonstrated to the concretization of the fundamental right to labor union liberty in Brazil.